Self-Medication with Antibiotics during COVID-19 in the Eastern Mediterranean Region Countries: A Review - Feras Jirjees; Munazza Ahmed; Somayeh Sayyar; Monireh Amini; Hala Al-Obaidi; Mamoon A. Aldeyab (MDPI AG, 2022)
Self-treatment with medicines including treatment with antibiotics is a growing global concern, as it can cause public health problems, such as antibiotic resistance and drug toxicity. Therefore, the significance of the self-medication impact of COVID-19 in any region can have an influence on the prevalence of such problems. The review aimed to investigate the self-treatment with antibiotics among the general population in Eastern Mediterranean region countries during COVID-19 pandemic. A comprehensive review of literature in four databases was conducted for the pandemic period from January 2020 to the end of March 2022. Nine studies related to self-treatment with antibiotics were found. The studies were homogeneous in terms of assessing the antibiotic self-treatment usage during the COVID-19 pandemic among the general population and among community pharmacies. The prevalence of self-treatment with antibiotics ranged from 20.8% to 45.8% between the studies. The main reasons for that were cost-saving, fear of COVID-19 infection, quarantine, and ease of accessibility without time limits. Antibiotic self-treatment has been high during the COVID-19 pandemic; however, it was less reported during the study period than before the time of the pandemic. There is a need for more restrictions on dispensing antibiotics from community pharmacies. In addition, there is a need to raise awareness among the population regarding self-treatment with antibiotics.